Light yield and field dependence measurement in PandaX-II dual-phase xenon detector. (5th January 2022) - Huang, Z.; Abdukerim, A.; Bo, Z.; Chen, W.; Chen, X.; Chen, Y.; Cheng, C.; Cheng, Y.; Cui, X.; Fan, Y.; Fang, D.; Fu, C.; et al.
Abstract: The dual-phase xenon time projection chamber (TPC) is one of the most sensitive detector technology for dark matter direct search, where the energy deposition of incoming particle can be converted into photons and electrons through xenon excitation and ionization. The detector response to signal energy deposition varies significantly with the electric field in liquid xenon. We study the detector's light yield and its dependence on the electric field in the PandaX-II dual-phase detector containing 580 kg liquid xenon in the sensitive volume. From our measurements, the light yield at electric fields from 0 V/cm to 317 V/cm is obtained for energy depositions up to 236 keV.